Strengthening Civic Disposition Through Learning Media Utilization PosTer (Best Posting) In Instagram - Veronika Susanti Suban; Mukhamad Murdiono; Chandra Dewi Puspitasari (Journal of Social Research, 2024)
This article aims to find out the utilization of social media-based learning media, namely PosTer (best post) in instagram in strengthening civic disposition. The research method used is descriptive qualitative method. The research subjects were students of class E of the Mathematics Study Program, Yogyakarta State University. Data collection techniques and instruments used observation, interviews, and documentation. Data analysis used qualitative data analysis interactive model. Data validity tests include credibility, transferability, dependability, and confirmability tests. The results showed that the application of PosTer media in instagram in Pancasila Education lectures was carried out through three stages, namely explaining the learning topic, determining the value theme, posting in instagram, and the assessment stage carried out in the core activities of the lecture. The application of PosTer media in instagram can strengthen student's civic disposition which includes the characters of tolerance, peace-loving, creative, communicative, responsibility, discipline, and critical thinking. Therefore, it can be concluded that this media can be used in learning to strengthen student's civic disposition.